Asian American and Pacific Islander Access to Abortion During COVID-19: A Complex Interplay of Factors (Mary Ann Liebert, 2022)
Often stereotyped as the ?model minority,? health care providers, lawmakers, and the general public regularly underestimate and ignore the health concerns of Asian American and Pacific Islanders (AAPIs). The COVID-19 pandemic has exposed the racism that AAPIs face?many communities report facing severe xenophobia during the pandemic, which has increased hesitancy to obtain needed medical treatment and heightened mental health issues at a time of isolation. The pandemic is also exacerbating the barriers that already exist in accessing abortion care?with travel restrictions, quarantine measures, lesser availability of appointments, and more burden on the health care staff and system. There has been no discussion on the impact of the pandemic on AAPIs' access to abortion care. We discuss challenges that are specific to AAPIs in accessing sexual and reproductive care, especially abortion, and how these are compounded by the lack of appropriate data and methods. We then discuss the added complexity that comes with accessing abortion care during a pandemic and provide recommendations for research methods to better reach these populations.